The role of religion in heart-transplant recipients' long-term health and well-being - Harris, Ronna Casar (Journal of religion and health, 1995)
While religion has long been recognized clinically to provide important coping strategies in the face of serious health problems, there has been little systematic consideration of its role in organ transplant recipients' long-term reactions and adjustment to this experience. This study examines these issues through qualitative and quantitative evaluation of longitudinal data collected from 40 adult heart recipients followed during their first year post-transplant. Large proportions of recipients expressed strong beliefs and were able to increase religious participation over the 12-month study period. They delineated specific ways in which their faith had provided them support, as well as ways in which the transplant experience itself further strengthened their beliefs. We found empirical evidence that recipients with strong beliefs who participated in religious activities had better physical and emotional well-being, fewer health worries, and better medical compliance by the final 12-month assessment. The findings suggest the development of specific nursing, social-service, or pastoral-involvement strategies, continuing staff education about the role of religion in patient care. The implications of such interventions for maximizing quality of life in transplant recipients are discussed.